Evaluación del flunixin meglumine y progesterona, versus el porcentaje de concepción de embriones frescos transferidos en receptoras vírgenes en varias ganaderías de la sierra ecuatoriana - Llumigusin Jacome, Hector Raul (2013)
With regard to embryonic losses representing between 30 and 40 % of the causes of poor reproductive performance in cattle ( Perez , R. , 2001 ) , several methods have been employed to increase conception rates embryonic and trying to raise the conception rate of Embryos transferred in vaconas fresh virgins. This research was conducted in five estates in different parts of the Andean Highlands, the objective of this study was to evaluate whether the application of Flunixin Meglumine, progesterone, and their combination increases the conception rate in vaconas virgins. We used 20 vaconas virgin Holstein and Brown Swiss, after being synchronized four treatments were applied : T1 , 500mg IM Meglumine Flunixin exact time after Embryo Transfer ( n = 5 ) , T2 , Progesterone 200mg IM exact time after Embryo Transfer (n = 5); T3 Combination treatments 1 and 2 (n = 5); T4 Control Group (n = 5)....